Kualitas dan Fungsi Ruang Terbuka Hijau di RPTRA Taman Matoa Jagakarsa (International Forum of Researchers and Lecturers, 2025)
This study aims to evaluate the quality and function of Green Open Space (RTH) at RPTRA Taman Matoa, Jagakarsa. The background of this paper is the importance of RTH in urban planning as an open interaction space for the community. This research was conducted using normative and empirical research methods to collect data on the physical condition, utilization, and community perceptions of the RTH. This RTH functions as a place for recreation, sports, and social activities for the surrounding community. These findings indicate that good management of RTH can improve the quality of the urban environment and community welfare.